Access and barriers to safer supply prescribing during a toxic drug emergency: a mixed methods study of implementation in British Columbia, Canada - Karen A. Urbanoski; Thea van Roode; Marion Selfridge; Katherine C. Hogan; James Fraser; Kurt Lock; Phoenix Beck McGreevy; Charlene Burmeister; Brittany Barker; Amanda Slaunwhite; Bohdan Nosyk; Bernadette Pauly (BMC, 2024)
Abstract Background In March 2020, British Columbia, Canada, introduced prescribed safer supply involving the distribution of pharmaceutical grade alternatives to the unregulated toxic drug supply. Prior research has demonstrated positive impacts on overdose mortality, but with limited reach to people who use substances. Objectives of this study were to (1) identify barriers to accessing safer supply prescribing among people who use substances; and (2) determine whether and how barriers differed between people with and without prescriptions, and between urban and rural settings. Methods We conducted a participatory mixed-methods study guided by the Consolidated Framework for Implementation Research. Participants (≥ 19 years old) had received a safer supply prescription or were seeking one (survey n = 353; interviews n = 54). Results Participants who had a prescription were more likely to be living in a large urban centre, compared to medium/smaller centres and rural areas (78.5% vs. 65.8%, standardized mean difference = 0.286). Participants who did not have a prescription were more likely to report an array of structural, interpersonal, and health-related barriers (compared to those who had a prescription). In interviews, participants linked experiences of barriers to stigma and criminalization, low availability of services, lack of information and prescribers, not being able to get what they need, and anxieties, worries and doubts stemming from personal circumstances. There were no notable differences between large urban centres and medium/smaller centres and rural areas in the presence of specific types of barriers. Conclusions Findings demonstrate restricted access to safer supply prescribing outside of large urban centres and provide future targets for enhancing implementation. Attention is needed to promote equity and counter systemic barriers in the implementation of responses to the ongoing toxic drug emergency.